Aerosol size distribution and gaseous products from the oven-controlled combustion of straw materials - Calvo, Ana I. (2011)
A number of controlled combustions have been carried out in the laboratory using samples of oats and barley straw collected in Spain in order to establish the characteristic particle spectra of these emissions. In addition, chemical compounds such as CO2, NO2 and NO and gravimetric variations have been registered during the combustion processes. For each combustible the burning phase has also been defined. Burning barley generates a higher number of particles in the fine mode (with a diameter of less than 0.5 μm) than oats (74% vs. 59%). The distributions of particles emitted during the flaming phase have been characterized, as well as during the previous and subsequent phases. The average geometric diameter reached its maximum during the flaming phase, with 0.53 ± 0.10 μm and 0.44 ± 0.04 μm for oats and barley, respectively. After the flaming phase, oat straw generates coarser particles than barley.